Energi Terbarukan dalam Perspektif G20: Peluang dan Tantangan - Saraswati, Dini Putri; Darmastuti, Shanti; Juned, Mansur; Utami, Rahmadini; Talmullah, Ali (Program Studi Magister Manajemen Lingkungan, 2024)
The climate crisis, which also disrupts global stability, forces countries to make an energy transition towards renewable energy. A multilateral forum consisting of 19 countries and the European Union, the G20 has a strategic role to play in promoting the issue of the energy transition. Moreover, all of its member countries are among the largest non-renewable energy consumers in the world. However, of course, not all of the G20 member countries consist of developed countries. Therefore, they have their own challenges and opportunities. This paper will explain the opportunities and challenges of the energy transition by G20 member countries, especially developing countries. The country samples taken were Indonesia, Brazil, India, Saudi Arabia, and China. The method used is a qualitative research method by conducting an interview with an informant and studying documents. The results of the research show that the member states of G20, especially developing countries, still face challenges in the energy transition.